The Transformation of Modern Markets into Digital Markets A Case Study on MSME Actors in Gunungsitoli City - Nov Elhan Gea; Odaligoziduhu Halawa (CV. HEI PUBLISHING INDONESIA, 2025)
The rapid development of information and communication technology has significantly transformed the business landscape, particularly through the emergence of digital markets that offer convenience and efficiency in transactions. In Gunungsitoli City, this transformation presents serious challenges for Micro, Small, and Medium Enterprises (MSMEs). A 2024 survey revealed that 68% of MSME actors experienced a decline in sales over the past two years, mainly due to fierce price competition and the rise of digital-based services. Additionally, 57% reported difficulties competing with large e-commerce platforms, while 45% had not fully adopted digital technology in their operations. This lack of digital adaptation, combined with limited access to technology and low digital literacy, has weakened their competitiveness and market presence. As a result, 40% of MSMEs have considered closing their businesses due to declining turnover. Despite these challenges, digital transformation also offers opportunities to increase efficiency and expand market reach. This research aims to analyze the impact of digital market transformation on MSMEs in Gunungsitoli and identify practical strategies to support their adaptation and sustainability in the digital era. The findings are expected to assist stakeholders in formulating effective policies and programs to strengthen local MSMEs and enhance their competitiveness the evolving digital economy.